PENYULUHAN DAMPAK KLORIN TERHADAP KESEHATAN DAN CARA PEMERIKSAANNYA DI WILAYAH DESA PARANGBADDO KECAMATAN POLONGBANGKENG UTARA KABUPATEN TAKALAR - Jangga Jangga; Saparuddin Latu; Surya Syarifuddin (JURNAL PENGABDIAN MANDIRI, 2022)
Tissue is very important to the global community because it serves many purposes. Tissue contain chemicals that can migrate into food. The chlorine bleaching agent used to make the tissue look white and clean turns out to be carcinogenic, and if it enters the body, it can cause a variety of diseases. This activity was carried out by empowering the community by involving health center officers and the community in the Parangbaddo Village area, North Polongbangkeng District, Takalar Regency to conduct counseling and examination of chlorine contained in tissue using qualitative methods. This activity was carried out on January 15, 2022 at the Parangbaddo Village Office, North Polongbangkeng District, Takalar Regency. The community in the Parangbaddo Village Area, North Polongbangkeng District, Takalar Regency is the target of this activity. The results showed that the tissue was positive for chlorine, due to the red color after adding DPD reagents. Counseling activities are carried out to provide information about the impact of chlorine and health problems that will be caused.